2018
DOI: 10.5812/iranjradiol.57623
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Chemotherapy Response in Primary Osteosarcoma by Use of the Multifractal Analysis of Magnetic Resonance Images

Abstract: Background: Due to the high level of cytogenetic heterogeneity in osteosarcoma, personalized treatment is the promising strategy for the improvement in outcomes. This is currently not possible due to the absence of targeted therapies and reliable predictors for response to induction chemotherapy. Objectives: To investigate the predictive value of computational analysis of osteosarcoma magnetic resonance (MR) images. Patients and Methods:Multifractal analysis was performed on MR images of primary osteosarcoma o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Alike other cancer types, it occurs due to genetic disorder and is not mostly connected to familial traits [2]. However, in one of the studies conducted earlier, osteosarcoma was found to have association with familial retinoblastoma cases i.e., family history is concerned with adolescent cancer in eye [3]. The symptoms of osteosarcoma disease include aches from the affected bone in the beginning while as time goes by, the low level of pain occurs and the patient's agony increases.…”
Section: Introductionmentioning
confidence: 98%
“…Alike other cancer types, it occurs due to genetic disorder and is not mostly connected to familial traits [2]. However, in one of the studies conducted earlier, osteosarcoma was found to have association with familial retinoblastoma cases i.e., family history is concerned with adolescent cancer in eye [3]. The symptoms of osteosarcoma disease include aches from the affected bone in the beginning while as time goes by, the low level of pain occurs and the patient's agony increases.…”
Section: Introductionmentioning
confidence: 98%